Penerapan Teknologi Informasi dalam Pemasaran dan Pengolahan Persediaan CV. Diwarna - Darmanto; Agus Prayitno; Dhaniswara, Erwin (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
This Community Partnership Empowerment Program is carried out by the implementing team with CV Diwarna Partners who produce Socks and embroidery products for institutional attributes. In conditions where the production process can be completed quickly and abundantly, it requires efficient and healthy marketing, production and financial management. Partners' priority issues relate to marketing access, productivity, and readiness in the digital ecosystem. For this reason, the ability to increase production is directed by planning and market segmentation. Digital marketing strategies can be used to strengthen market segmentation and reach a wider market. The purpose of this program is to increase the role of Information Technology in marketing and production management. The method of implementation includes socialization, training, application of information technology, mentoring and evaluation. The results obtained are in the form of support for inventory information system applications and digital marketing, as well as increasing the ability and digital literacy of leaders and employees in using these applications. Overall, the contribution of facilities and applications built for partners has a good level of acceptance with an average score of 76% Keywords: Information Technology, Digital Marketing, Inventory Management